Leg muscle strength is reduced in PD and relates to the ability to rise from a chair - Inkster, Lisa M (2003)
Individuals with Parkinson’s disease (PD) have difficulties rising from a chair; however, factors contributing to this inability have never been investigated. This study compared lower extremity strength between individuals with PD and healthy controls and quantified the relationships between strength and the ability to rise from a chair. Ten males with mild PD and ten male age-matched controls performed maximal concentric, isokinetic knee and hip extensor torque on an isokinetic dynamometer to quantify muscle strength. Subjects also rose from a chair at their comfortable pace without the use of their arms and the duration of this task provided a measure of sit-to-stand (STS) ability. Subjects with PD were tested in an on- and off-medication state on different days. Mean hip and knee extensor torques were less in subjects with PD, with greater deficits found at the hip. Greater hip strength was related to better STS ability in subjects with PD while greater knee strength was related to better STS ability in controls. These results show that individuals with mild PD generate smaller extremity forces compared to controls. Reduced strength, particularly at the hip, may be one factor that contributes to the difficulty of persons with PD to rise from a chair.